Selecting an Appropriate Animal Model for Dyslipidemia - Mallya, Pooja; Lewis, Shaila A (Indian Journal of Pharmaceutical Education and Research, 2024)
In recent years, dyslipidemia, a major risk factor for cardiovascular diseases is on the rise globally due to sedentary lifestyles and unhealthy diets. Though abundant data pertaining to the factors influencing dyslipidemia, the mechanism of action of various drugs and the pathogenesis of the disease are available in the literature, the disease is poorly understood. Animal models play a crucial role in investigating the pathophysiology and aid in developing effective formulations. Despite extensive research being carried out in the arena of dyslipidemia, there is no adequate knowledge about the most suitable in vivo model. A systematic literature search was carried out to review the animal models such as rats, mice, rabbits and zebrafish models with chemical-induced, diet-induced and drug-induced methods that have been used to study dyslipidemia. This review focuses on the mechanism involved in the dyslipidemia induction techniques explored by researchers along with their applications and limitations. The induction methods reported are expected to provide better insight in selecting an appropriate model to draw precise conclusions.
Keywords: Dyslipidemia; Animal models; Cardiovascular diseases; Animal research; High-fat diet; in vivo model